Sequentially Activated Smart DNA Nanospheres for Photoimmunotherapy and Immune Checkpoint Blockade - Yu Chen; Yu Guo; Wen Cheng; Jiahao Fan; Jiacheng Li; Jiajia Song; Xiaohai Yang; Kemin Wang; Jin Huang (Advanced Science)
Abstract Due to the inherent immunosuppression and immune evasion of cancer cells, combining photoimmunotherapy with immune checkpoint blockade leverages phototherapy and immune enhancement, overcoming mutual limitations and demonstrating significant anticancer potential. The main challenges include nonspecific accumulation of agents, uncontrolled activation, and drug carrier safety. Smart DNA nanospheres (NS) is developed with targeted delivery and controllable release of photosensitizers and immune agents to achieve effective synergistic therapy and minimize side effects. The multifunctional NS incorporate a targeting module for programming aptamers, a response module for programming i‐motif and DNA/RNA hybrid sequences, and a therapeutic module for packaging photosensitizers and PD‐L1 siRNA. NS navigate to the tumor site and are sequentially activated by intracellular acid and enzymes to release photosensitizers and programmed death ligand 1 (PD‐L1) small interfering RNA (siRNA)a. Besides tumor killing and immune promotion, activated NS downregulate PD‐L1 expression, alleviating immune tolerance and evasion, thus enhancing the immune response. These results indicate that NS significantly enhance antitumor immune responses, synergistically improve antitumor efficacy, and reduce systemic toxicity. This study broadens the application of DNA nanomaterials in precision drug delivery and tumor therapy.